Tissue Analysis as a Nutrient Management Tool for Bahiagrass Pastures - Maria L. Silveira; Joao M. Vendramini; Lynn E. Sollenberger; Cheryl L. Mackowiak; Yoana C. Newman (EDIS)
SL-252, a 3-page illustrated fact sheet by M.L. Silveira, J.M. Vendramini, L.E. Sollenberger, C.L. Mackowiak, and Y.C. Newman, explains the principles of tissue analysis, tissue sampling and handling, analysis and interpretation, and future directions. Published by the UF Department of Soil and Water Science, October 2007.